Intramuscular versus intradermal botulinum toxin for forehead wrinkles: a review of side effects and efficacy - Mohammed Almashali; Rahaf Almutairi; Asem Shadid (PAGEPress Publications, 2023)
Botulinum toxin type A (BTA) is a neurotoxin used for both cosmetic and non-cosmetic purposes. BTA is commonly administered as an intramuscular injection to treat wrinkles. However, when it comes to treating forehead wrinkles, IM is associated with a greater rate of ptosis. Intradermal injection is currently thought to be a better alternative. We searched PubMed and Google Scholar for research articles published between 1989 and 2023 using the following keywords: "intradermal," "intramuscular," "botulinum toxin," and "forehead wrinkle." The search yielded three randomized controlled trials and a double-blind, split-face case report on 58 patients. We found that although intradermal and intramuscular injections have symmetrical anti-wrinkle effects, the former results in a lower rate of ptosis and a greater degree of pain.